Women resisting terror: imaginaries of violence in Algeria (1966–2002). Issue 1 (1st January 2017) - Flood, Maria
ABSTRACT: This article charts the roles and representations of Algerian Women as both agents and victims of violence in the War of Independence (1956–1962) and the Algerian Civil War of the 1990s in which the role of women emerged as a significant site of ideological, religious, and political struggle. This vision of Algerian Women, caught between models of participation and passivity, can be located within a long imaginary of Algerian women as exposed to colonial, patriarchal, state, or terrorist violence, but also possessing fortitude and resilience in the face of conflict. I examine the model of female agency through the figure of the bomb carrier in Gillo Pontecorvo's The Battle of Algiers (1966), illuminating the gap between the freedom depicted, and promised, and the reality of women's experience after the war. I then turn to the Algerian Civil War, considering one of the most enduring photographs to emerge from the conflict, Hocine Zaourar's La Madone de Benthala (1997), an image that inscribes a quasi-universal image of female victimhood. Finally, an exploration of Yamina Bachir-Chouikh's Rachida (2002) reveals a more complex staging of female resistance in times of terror. The film offers a delicate exploration of the emotional and psychological effects of political and symbolic violence, which troubles a more usual imaginary of Algerian women as noble, suffering, and endlessly resistant or resilient figures.